When you square each side of an equation, is the resulting equation equivalent to the original equation?
2 Answers | Add Yours
If you square both sides of an equation, do you get an equivalent equation?
The answer is no. Squaring both sides of an equation will occasionally introduce an "extraneous" solution; a solution for the modified equation that is not a solution to the original equation.
These occur often when dealing with logarithms and certain trigonometric functions. They can also occur when dealing with radical equations (or equations with rational exponents) amongst other types.
(1) ` ``sqrt(x)=-3 ` : this equation clearly has no solutions in the real numbers, as the square root of a real number is nonnegative if it exists. But squaring both sides yields x=9. But x=9 is not a solution to the original equation as `sqrt(9)=3 !=-3 ` .
(2)` `` `` `` ` `sqrt(x)=sqrt(x^2-2) ` : squaring both sides yields `x=x^2-2 ==> x^2-x-2=0 ==> x=2,-1 ` . x=2 is a solution to the original equation, but x=-1 (in the real numbers) is not since ` sqrt(-1) ` is not real.
(3) x+1=x-1: squaring both sides yields `x^2+2x+1=x^2-2x+1 ==> 4x=0 ==> x=0 ` . But x=0 is not a solution to the original "equation". (The original equation has no solutions.)
Please note that the definition of equivalent equations are equations with the same solution set.
It will not be equivalent across all values for the same equation
We’ve answered 319,647 questions. We can answer yours, too.Ask a question